Hb S (HBB: c.20A>T) Characteristics by High Performance Liquid Chromatography in Patients with Sickle Cell Disease Receiving the Novel Agent Voxelotor. (2nd November 2021) - Tsitsikas, Dimitris A.; Kamal, Mawlid; Braimoh, Adeyinka; Benson, Susan; Abukar, Jibril
Abstract: Voxelotor is a novel agent in the management of sickle cell disease. It is an inhibitor of Hb S ( HBB : c.20A>T) polymerization that reversibly binds to hemoglobin (Hb), stabilizing it in the oxygenated state that has been shown to reduce hemolysis and to improve anemia. Four patients in our institution are receiving treatment with Voxelotor as part of clinical studies. All four showed a characteristic change in the appearance of Hb S by high performance liquid chromatography (HPLC) soon after commencing treatment. A second peak was identified eluting at the Hb D window. Cellulose acetate membrane and agar gel electrophoresis only identified a band at the Hb S position. The patients' Hb level or clinical conditions were not adversely affected. Our findings indicate that patients receiving Voxelotor invariably display this unique pattern by HPLC. As there will be an increasing number of patients treated with this agent, it is important to be aware of this characteristic HPLC appearance for diagnostic and treatment monitoring purposes.